Guidelines for measuring gender transformative change in the context of food security, nutrition and sustainable agriculture - Food and Agriculture Organization of the United Nations; International Fund for Agricultural Development; World Food Programme; CGIAR GENDER Impact Platform (FAO; IFAD; WFP and CGIAR, 2023)
These Guidelines include step-by-step guidance to formulate qualitative and quantitative indicators of gender transformative change to help gender experts and food security, agriculture and nutrition programme specialists in their efforts to design, implement, monitor and evaluate gender transformative interventions. These indicators should be distinctive from and a complement to other reach, benefit and empower indicators intended to contribute to gender equality outcomes in food security, nutrition and sustainable agriculture.